Introduction - Shah, Muhammad Azeem Ali; Lautze, Jonathan F.; Meelad, A. (CAB International, 2023)
This chapter contextualizes the book’s aim and scope within global experiences in transboundary water management as well as regional realities of human development. The chapter rationalizes the focus on three of the nine rivers shared by Afghanistan and Pakistan, i.e., the Kabul, Kurram and Gomal, and identifies the new contribution that this book provides. Importantly, this is believed to be the first book to focus on the entirety of these three shared rivers—compiling and synthesizing data and information from both countries to distil key lessons and messages. The chapter proceeds to provide a cursory overview of the three basins to lay foundations for the more thorough elucidations in the chapters that follow. The chapter concludes with reflections on the significance of this book and its role in ameliorating conditions in the three basins.